PENGARUH KEPUASAN KERJA KARYAWAN TERHADAP KEINGINAN KELUAR KERJA (TURNOVER INTENTION) (Penelitian Pada Karyawan PT Pindad Persero Divisi Munisi) - Oni Vidya Pentasasi (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study aims to determine how much influence job satisfaction to employees desire to get out ofwork (turnover intention). Job satisfaction is a major factor in influencing someone to come out of the company where the employee works. This research is explanatory research. This study aims to clarify the effect of independent variables with the dependent variable by testing the hypothesis that has been created previously. In this study, the independent variables is job satisfaction consist of satisfaction with salary, satisfaction with the promotion, satisfaction with coworkers, satisfaction with supervisor, satisfaction with the work itself, while the dependent variable is a desire out of work (turnover intention). This research was conducted in PT.Pindad Persero Munition Division Turen Malang because of the many employees who want to quit work. The population in this study were permanent employees munitions division at PT Pindad totaling 753 people. In this study, conducted sampling using probability sampling methods so determined 88 respondents to be investigated. Data collection technique used questionnaire systematically arranged and standards. The data in this study using multiple linear regression analysis by F test and t test as hypothesis testing. Results showed that all independent variables consisting of satisfaction with salary, satisfaction with the promotion, satisfaction with coworkers, satisfaction with supervisor, satisfaction with the job itself simultaneously and partially significant effect on the desire out of work (turnover intention). The amount of R Square of independent variables to work out the desire (turnover  intention) employees  of  PT  Pindad  Munitions  Division  amounted  to  61.7% and  the remaining 38.3% is influenced by other variables that are not addressed in this study.Keywords: Regression, Job Satisfaction, Work Out Interest